Constructing metal-free heterophotocatalyst using two-dimensional carbon nitride sheets and violet phosphorene for highly efficient visible-light photocatalysis. (20th May 2023) - Wang, Yong; Zeng, Chengxin; Wu, Liting; Dong, Yalin; Zhang, Yu; Yang, Dingyi; Hu, Wen; Hao, Jian; Pan, Hongzhe; Yang, Rusen
Highlights: The built-in electric field of the p-n junction promotes the transport of photogenerated carriers at the heterojunction interface. The introduced VP served as the H2 and CO2 adsorption site and enhanced the adsorption capacity of 2D CNs/VP heterostructure. The CNs/VP heterophotocatalyst exhibited much higher visible-light photocatalytic hydrogen and CO generation rates than CNs under visible-light irradiation. Abstract: Two-dimensional (2D) carbon nitride sheets (CNs) with nanoscale thickness have great potential in solar energy conversion owing to their intrinsic bandgap. However, their photocatalytic efficiency falls far below the practical requirements because the generated electron-hole pairs rapidly recombine. We construct a metal-free 2D p–n junction heterophotocatalyst from CNs and violet phosphorene (VP) using a simple electrostatic self-assembly method. The experimental results and density functional theory calculations show that the built-in electric field of the p–n junction promotes photogenerated carrier transport at the heterojunction interface, thereby promoting the separation of photogenerated electron-hole pairs. Under visible-light illumination, the visible-light photocatalytic hydrogen and CO production rates of the CNs/VP heterojunction were increased by 5.85 and 1.51 times, respectively, when compared to that of CNs. This study provides new insights into the design of metal-free heterogeneous photocatalysts with high catalytic activity.